Benefits of Recovery and Partial Recrystallization of Nano‐Twinned Austenitic Steels. Issue 10 (20th June 2013) - Bouaziz, Olivier; Barbier, David
<x xml:space="preserve">Abstract</x> Grain refinement is efficient for developing single phase steel with high yield stress but with a detrimental effect on the strain hardening. To overcome this limitation, the exploitation of the thermal stability of mechanical twins in austenitic steels, combined to recovery or partial recrystallization treatments, are reviewed. Both strategies exhibit benefits for the strength/elongation balance, but recovery gives the best properties in austenitic steel. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>